You are on page 1of 10

# SIMULTANEOUS

EQUATION

2003P 2.1
Solve the simultaneous equations
4x + y = 8 and x2 + x y = 2.
[5 marks]

## Solve : 4x+y =-8 (1)

x2 +x -y =2 (2)

From (1)
Substitute in (2):

y = -8 - 4x
x2 + x (-8 4x ) = 2

## Simplify to get Q.E:

x2 + 5x + 6 = 0

Solve Q.E:

(x + 3) (x + 2) = 0

## The first unknown

-3
-2
x =....,

When x = -3,
x = -2,

y = -8 4(-3) = 4
y = -8 4(-2) = 0
3

SKILL 1
CHANGING THE SUBJECT OF THE FORMULA
examples

1) 3 x y 6 1) y 6 3x
2) 2 x y 3 2) y 2 x 3
3)

3
)
x

6
y

18
x
3y 9
x 18 6 y

2
4) 2 x 3 y 2
x
y
5)

1
2 3

2 3y
4) x
2

5) 3 x 2 y 6
6 3x
y
2

SKILL 2
Expansion of Algebraic equation to get quadratic equation
ax2+bx+c=0
examples

(a b) a 2ab b
2

(a b) a 2ab b
2

( x 2) x 4 x 4
2

( x 2) 2 x 2 4 x 4
(3 x 2 y ) 9 x 12 xy 4 y
2

(5 2 y ) 2 25 20 y 4 y 2

SKILL 3
ax2+bx + c = 0

examples
1

Solve

Example
By using formula
Solve

x2 3x 10= 0

2 x2 8x 7 0

By factorization

(x + 2)(x 5) = 0

x = -2, x = 5

8 (8) 2 4(2)(7)
x
2(2)

2.707 or

1.293

2 x 3 y 10 (1)

Example 1

2
3
2 y 3x

5
5 2 y 3 x 5 xy ( 2)
x
y
xy
x

From (1)
Substitute in (2):
Simplify to get Q.E:

Solve Q.E:
The first unknown
When y =
y=

,
,

10 3 y
2

10 3 y
10 3 y
2 y 3
5
y
2
2

From (1)
Substitute in (2):
Simplify to get Q.E:

When y =
y=

,
,

## Solve the simultaneous equations

2
2

y x 3 0 and 2 x 3 y 13
[5 marks]

y x 3 0 (1
1))

y x3

(1)

2 x 2 3 y 2 13 (2) 2 x 2 3 y 2 13 ( 2)

2 x 2 3 x 32 3

P1

K1

2 x 2 3 x 2 6 x 9 13
2

2 x 3 x 18 x 27 13 0
2

5 x 18 x 14 0
18 182 4(5)(14)
x
2(5)
N1
x 1.14, 2.46

K1

When x 1.14,

y 1.14 3 1.86,

x 2.46,

y 2.46 3 0.54

N1